PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING BERBANTUAN MULTIMEDIA TERHADAP HASIL BELAJAR IPA - Rasni Karwati, Ni Pt; Wiyasa, Km Ngurah; Ardana, I Kt (Universitas Pendidikan Ganesha, 2018)
This research aims to determine the significance of the difference in science learning results between the group of fifth-grade students in Gugus I Elementary Schools, North Kuta District, in the school year of 2017/2018, that take lessons with the multimedia-assisted probing-prompting learning model and the group of students that take lessons with the conventional learning. The design of this research is a quasi-experimental research with the nonequivalent control group design. The population of this research are all the fifth-grade students of Gugus I Elementary Schools in North Kuta District that still implement the KTSP, which consists of 10 classes with a total of 339 students. The sampling is conducted using the random sampling technique. The sample in this research are the students of class VB in SD (Elementary School) No.7 Dalung, with 36 students as the experiment group and the students of class VB in SD No.4 Dalung with 28 students as the control group. The data collection is conducted using the test method in the form of the multiple choice objective test. The science learning results are analyzed using the t-test. Based on the average the experiment groups =80,89 > the control group =72,85, which means that the multimedia-assisted probing-prompting learning model has an influence on the science learning result. Based on the hypothesis test, tvalues =4,517> ttable =2,000, with dk=62 and a significance level of 5%. Based on the test criteria, H0 is rejected and Ha is accepted. Thus, it can be interpreted there is a significant difference the science learning result between the group of students that were taught using the multimedia-assisted probing-prompting learning model and the students that were taught using the conventional learning. It can be concluded that the the multimedia-assisted probing-prompting learning model has an influence on the science learning result of the fifth-grade students in Gugus I Elementary School, North Kuta District, in the school year of 2017/2018. Keywords : probing prompting, multimedia, science learning result